The Entrepreneurship Action of Independent Gaming Producers Inspired in the Effectuation - Gomes, Jardiel de Moura; Paiva Júnior, Fernando Gomes de; Xavier Filho, Jose Lindenberg Julião (REGEPE Entrepreneurship and Small Business Journal, 2019)
Objective: This study aims to unveil the entrepreneurial action of independent game producers. Method: A qualitative research was carried out with four semi-structured interviews, analyzed through the technique of thematic content analysis. Originality / Relevance: The study was distinguished by conciliating effectuation with entrepreneurial action and allows the understanding of how this actor articulates through business artifacts, technological platforms and digital infrastructure. Results: The results reveal the articulation of strategic actors in the midst of organizational networks as social action form that is based on partnership building and maintaining and shared values strengthening. Theoretical / methodological contributions: Two theoretical approaches were defined: the effectuation, proposed by Sarasvathy (2001) and the entrepreneurial action, developed by Paiva Junior (2004). These complementary approaches contemplate a new way of analyzing entrepreneurial action.